Agricultural biodiversity and elimination of hunger and poverty: UN Millennium development goals: five years later: the Chennai Platform for Action - International Plant Genetic Resources Institute (2005)
This booklet presents the 'Chennai Platform for Action' to enhance the contribution of plant genetic resources to meeting the Millennium Development Goals (MDGs), especially to reducing hunger and poverty. The action plan described in this booklet is intended to help national governments and international agencies to achieve the goal of halving hunger and poverty by 2015. It promotes the principles of giving agricultural biodiversity greater importance in national and international development strategies and creating the required enabling policy conditions for the sustainable utilization of this treasure for the benefi t of the poorest and marginalized members of our society. The action plan calls for increased international collaboration in the conservation and sustainable and equitable sharing of the benefi ts arising from the use of agricultural biodiversity. It underlines the urgent need for action in nationally appropriate ways for meeting the MDGs.